Human Hyaluronidase PH20 Potentiates the Antitumor Activities of Mesothelin-Specific CAR-T Cells Against Gastric Cancer - Zhao, Ruocong; Cui, Yuanbin; Zheng, Yongfang; Li, Shanglin; Lv, Jiang; Wu, Qiting; Long, Youguo; Wang, Suna; Yao, Yao; Wei, Wei; Yang, Jie; Wang, Bin-Chao; et al. (Frontiers in Immunology, 2021)
T cell infiltration into tumors is essential for successful immunotherapy against solid tumors. Herein, we found that the expression of hyaluronic acid synthases (HAS) was negatively correlated with patient survival in multiple types of solid tumors including gastric cancer. HA impeded in vitro anti-tumor activities of anti-mesothelin (MSLN) chimeric antigen receptor T cells (CAR-T cells) against gastric cancer cells by restricting CAR-T cell mobility in vitro. We then constructed a secreted form of the human hyaluronidase PH20 (termed sPH20-IgG2) by replacing the PH20 signal peptide with a tPA signal peptide and attached with IgG2 Fc fragments. We found that overexpression of sPH20-IgG2 promoted CAR-T cell transmigration through an HA-containing matrix but did not affect the cytotoxicity or cytokine secretion of the CAR-T cells. In BGC823 and MKN28 gastric cancer cell xenografts, sPH20-IgG2 promoted anti-mesothelin CAR-T cell infiltration into tumors. Furthermore, mice infused with sPH20-IgG2 overexpressing anti-MSLN CAR-T cells had smaller tumors than mice injected with anti-MSLN CAR-T cells. Thus, we demonstrated that sPH20-IgG2 can enhance the antitumor activity of CAR-T cells against solid tumors by promoting CAR-T cell infiltration.